Magyar-egyiptomi kapcsolatok a második világháború után (1947-1955) - J. Nagy László (Belvedere Meridionale, 2015)
The Hungarian-Egyptian relations have a long past and between the two world wars they become definitely manifold. After suffering an eclipse, the interest of in each other restarted from 1947. In the next decade, which was a determinant period in the history of both countries, in addition to political ones, economic, cultural and sport contacts dominated the bilateral relations. From the reports of the Hungarian ambassadors, some interesting details of the Egyptian history unfolds.